1997
DOI: 10.1007/bf00053023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KT-362, a sarcolemmal and intracellular calcium antagonist, on calcium transients of cultured neonatal rat ventricular cells: A comparison with gallopamil and ryanodine

Abstract: We evaluated the effects of KT-362 (5-[3-([2-(3,4-dimethoxyphenyl)-ethyl]amino)-1-oxopropyl]-2,3,4,5, -tetrahydro-1,5-benzothiazepine fumarate), a putative intracellular calcium antagonist, on the intracellular free calcium concentration ([Ca2+]i) of cultured neonatal rat ventricular cells using microfluorometry of fura-2. The effects were compared with those of gallopamil (D-600), a sarcolemmal calcium channel antagonist, and ryanodine, a modulator of sarcoplasmic reticulum (SR) function. KT-362 decreased bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Reports have suggested that this compound can affect plasmalemma NCX (Czyz and Kiedrowski, 2003) and L-type Ca 2ϩ channels (Thu et al, 2006). Various benzothiazepines with relatively different side chains, such as K201 (Kohno et al, 2003;Hunt et al, 2007) and KN-362 (Kodama et al, 1988;Tatsukawa and Arita, 1997), are known to modulate RyRs. K201 was also found to block the SERCA (Loughrey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have suggested that this compound can affect plasmalemma NCX (Czyz and Kiedrowski, 2003) and L-type Ca 2ϩ channels (Thu et al, 2006). Various benzothiazepines with relatively different side chains, such as K201 (Kohno et al, 2003;Hunt et al, 2007) and KN-362 (Kodama et al, 1988;Tatsukawa and Arita, 1997), are known to modulate RyRs. K201 was also found to block the SERCA (Loughrey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…30 µM KT-362 increased time to peak of the Ca 2+ transient, while the half-life of the calcium transient was prolonged at 10 µM and above. These effects of KT-362 on Ca 2+ transients could be mimicked by simultaneous application of 1 µM D600 and 10 µM ryanodine, suggesting that KT-362 inhibits both sarcolemmal calcium channels and calcium release channels of the sarcoplasmic reticulum [105]. Other studies also support the inhibition of calcium release channels of the endoplasmic reticulum (inositol-triphosphate receptor) by KT-362 in the micromolar range in rabbit aorta [191] and in canine femoral arteries [192].…”
Section: Brl-32872mentioning
confidence: 88%
“…The other one is the calcium content of the intracellular calcium stores not to mention the sarcoplasmic reticulum gain which relates the amount of released calcium to the amount of the triggering calcium [101], [102]. These two factors are both reduced by CCAs, therefore it is not surprising that CCAs lead to the decrease of calcium transient amplitudes (for verapamil and mibefradil [103] for D600 [104], for SR33805 [40], for KT-362 [105] and for AH-1058 [106]). The major ATP using process in myocytes is the contractile machinery, the activity of which depends on intracellular calcium.…”
Section: Potential Mechanisms Behind the Antiarrhythmic Actions Of Ccasmentioning
confidence: 99%